2015
DOI: 10.2147/ceg.s76579
|View full text |Cite
|
Sign up to set email alerts
|

Value of portal venous system radiological indices in predicting esophageal varices

Abstract: IntroductionPortal hypertension results from increased resistance to portal blood flow and has the potential complications of variceal bleeding and ascites. The splenoportal veins increase in caliber with worsening portal hypertension, and partially decompress by opening a shunt with systemic circulation, ie, a varix. In the event of portosystemic shunting, there is a differential decompression across the portal vein and splenic vein (portal vein > splenic vein), with a resultant decrease in the ratio of porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Portal hypertension is one of the most common complications of HHT. It is associated with higher portal vein diameter [27, 28] and lower portal vein velocity [29, 30] within the liver. As showed in Figs 1–3, in the estimated high-risk group 1 the intrahepatic portal vein diameter was significantly higher, while portal vein peak velocity was significantly lower than in group 2.…”
Section: Discussionmentioning
confidence: 99%
“…Portal hypertension is one of the most common complications of HHT. It is associated with higher portal vein diameter [27, 28] and lower portal vein velocity [29, 30] within the liver. As showed in Figs 1–3, in the estimated high-risk group 1 the intrahepatic portal vein diameter was significantly higher, while portal vein peak velocity was significantly lower than in group 2.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate becomes alarmingly high in this condition and around 20% of patients develop fetal complications. 15,16 This study only included patients with portal vein diameter more significant than 13cm. Our results revealed that patients with portal vein diameter above 13 mm had a high frquency of esophageal varices.…”
Section: Discussionmentioning
confidence: 99%
“…It also carries the risk of bleeding due to manipulation, as proved by a study in 2015. 15 Only 30-40% of patients with compensated cirrhosis were found to have gastro-oesophageal varices on screening endoscopy. 19 USG may therefore be a more cost-effective and non-invasive method to routinely screen patients at high risk for the presence of varices, to reduce the increasing burden and procedure costs of endoscopy units.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,10 These alternate procedures include Doppler USG, CT, MRI and Angiography. 11 In addition to these Platelet count is also a noninvasive parameter with high accuracy for the prediction of esophageal varices as cirrhotic pts having esophageal varices usually have a platelet count of < 100,000/cmm. 3 As a matter of fact there is quite a low chance of esophageal varices in cirrhotics having high platelet count a fact which enables us to avoid costly methods of screening such pts for esophageal varices.…”
Section: Guidelines Published By Baveno V1 Consensusmentioning
confidence: 99%
“…15 Various risk factors for variceal hemorrhage from esophageal varices include; size, presence of red sign, child classification, alcohol intake and local changes in distal esophagus such as GERD. 11 In view of the dreadful outcome of this life threatening disease, early detection and treatment even prophylactic, is vital in improving the outcome in these patients as this will lower down the upper Gl related mortality. 17,18 For this purpose alternative noninvasive methods instead of endoscopy are now being preferably used.…”
Section: Guidelines Published By Baveno V1 Consensusmentioning
confidence: 99%